1999
DOI: 10.1128/aem.65.5.2103-2111.1999
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-Modifying Enzymes of Flavodon flavus , a Basidiomycete Isolated from a Coastal Marine Environment

Abstract: A basidiomycetous fungus Flavodon flavus (Klotzsch) Ryvarden (strain 312), isolated from decaying sea grass from a coral lagoon off the west coast of India, mineralized nearly 24% of14C-labeled synthetic lignin to14CO2 in 24 days. When grown in low-nitrogen medium (2.4 mM N) this fungus produced three major classes of extracellular lignin-modifying enzymes (LMEs): manganese-dependent peroxidase (MNP), lignin peroxidase (LIP), and laccase. Low MNP and laccase activities were seen in high-nitrogen medium (24 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(20 citation statements)
references
References 53 publications
3
15
0
2
Order By: Relevance
“…1999). The results were consistent with the work by Raghukumar et al (1999) and Kondo et al (2004) who demonstrated the ability of some coastal and marine fungi to produce major lignocellulolytic enzymes at various culture growth conditions. The amounts of Lac, LiP and MnP are comparable to the amounts produced by the Tanzania's terrestrial fungi (Mtui et al 2003, Mtui andNakamura 2004).…”
Section: Figuresupporting
confidence: 92%
“…1999). The results were consistent with the work by Raghukumar et al (1999) and Kondo et al (2004) who demonstrated the ability of some coastal and marine fungi to produce major lignocellulolytic enzymes at various culture growth conditions. The amounts of Lac, LiP and MnP are comparable to the amounts produced by the Tanzania's terrestrial fungi (Mtui et al 2003, Mtui andNakamura 2004).…”
Section: Figuresupporting
confidence: 92%
“…Some fungi showed twin peaks in their enzyme activities during decomposition, which was similar to the results of some white rot fungi (Arora and Gill 2000;Raghukumar et al 1999;Ruttimann et al 1992). Reappearance of enzyme activity during the later days of leaf litter degradation might be ascribed to fungal autolysis resulting in the release of intracellular enzymes into the culture.…”
supporting
confidence: 80%
“…Novel fungi producing ligninolytic enzymes were isolated from different sources, such as sea grass, mud, herbaceous weed, and mangrove forests [99][100][101][102]. A marine-derived strain, Pestalotiopsis sp.…”
Section: Fungal Strains Effective For Laccase Production From Agriculmentioning
confidence: 99%